2018
DOI: 10.4317/jced.54904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatments on the bond strength of CAD/CAM fiberglass posts

Abstract: BackgroundThere is no ideal protocol for the surface treatment of fiber posts, especially when using a computer-aided design/computer-aided manufacturing (CAD/CAM) experimental fiberglass block. The purpose of this study was to evaluate the bond strength of a CAD/CAM customized glass fiber post and core after applying different surface treatment techniques.Material and MethodsForty premolars were prepared to receive a customized CAD/CAM glass-fiber post and core obtained from an experimental block of glass fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The customized post in this study was constructed of unidirectional glass fiber that was created using CAD-CAM technology without any extra interfaces, which might favour the stress distribution to the root. 1,11 The first hypothesis was accepted after it was demonstrated that well-adapted CAD-CAM glass fiber posts had significantly superior bond strength to root canal dentin in comparison to the prefabricated post cemented with the same self-adhesive resin cement. This may be due to the CAD-CAM post group's good adaption, which results in a thin and homogeneous resin cement coating with fewer voids and gaps between the cement and the root dentin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The customized post in this study was constructed of unidirectional glass fiber that was created using CAD-CAM technology without any extra interfaces, which might favour the stress distribution to the root. 1,11 The first hypothesis was accepted after it was demonstrated that well-adapted CAD-CAM glass fiber posts had significantly superior bond strength to root canal dentin in comparison to the prefabricated post cemented with the same self-adhesive resin cement. This may be due to the CAD-CAM post group's good adaption, which results in a thin and homogeneous resin cement coating with fewer voids and gaps between the cement and the root dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has shown that this method of surface treatment, at this concentration and time, will partly remove the epoxy resin covering of the glass fiber post, uncovering the glass fibers (without harming the post architecture), allowing for silanization and resin cement bonding. 1,26,27 In the current study, we used a self-adhesive resin cement because of the less clinical time required and also less sensitive technique than traditional resin cements, which required the use of adhesive systems. It also had superior dentin retention due to chemical reactions between both the functional methacrylate phosphoric acid esters and the hydroxyapatite present in the dentin .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simple procedures are indicated, such as use of 70% alcohol during cleaning of the posts and use of an universal adhesive. Different surface treatments of CAD/CAM glass fiber posts with 24% hydrogen peroxide and a moisture of silane and ethanol solution did not influence in bond strength values 7,8 .…”
Section: Introductionmentioning
confidence: 86%